Crescimento de nano tubos de carbono a partir do metano sobre catalisadores de cobalto suportados. - Oliveira, Hugo Alvarenga (2008)
Due to its exceptional physical and chemical properties, in a structure of nanometric size, carbon nanotube (CNT) can generate a great possibility of applications: added in plastics, the nanotubos can harden or become them conducting of electricity; for being extremely small e light, can arrive at the interior of a cell and be used as sensory for medical diagnostics, and the most promising of them is that the nanotubes will substitute the silicon in the age of the nanoelectronic. The grow of the CNTs was made by methane chemical vapor deposition on cobalt catalysis with 1 and 4wt. % supported in four different supports: Al2O3, Nb2O5, TiO2 and SiO2. The X-ray diffraction analyses had allowed the identification of supports crystalline phases, however, it was not possible to identify the structures of cobalt due to its low content. Nevertheless, through the Temperature Programmed Reduction analyze was possible to estimate the amount of Co3O4 in the catalysts and the degree of reduction. Two different types of pre-treatment were used for the catalyst activation, called condition 1 and condition 2, aiming to modify the morphology of the catalytic particle in order to modify the production of CNT. Under condition 1, where the catalysis were reduced since the room temperature until the reaction temperature (700°C), the catalysts presented greater dispersion and metallic surface area compared to condition 2, where the reduction was made isothermically at 700°C for thirty minutes. Both temperature programmed oxidation and Raman spectroscopy allowed to identify and quantify each form of carbon produced. The analyses of Raman help the identification of the nature of each oxidation peak observed in the profile of the TPO. The catalysts with the biggest production of CNT had been the supported on Al2O3 and SiO2, whereas, the catalysts supported on TiO2 and Nb2O5, presented lower activity due to the covering of the particle of cobalt for the support. However the catalysts supported in TiO2 presented greater selectivity for the SWNT.